Kajian Daerah Sulit Air di Kabupaten Kulon Progo Daerah Istimewa Yogyakarta - Hendrayana, Heru; Riyanto, Indra Agus; Nuha, Azmin (UNIVERSITAS NEGERI MAKASSAR, 2021)
Water-scarce areas can be identified from geology, meteorology, water installations, and drought conditions in the area. All of these aspects can be found in Kulon Progo Regency. The aim of this research is to identify water scarcity areas in Kulon Progo Regency and to determine priorities areas for building up some deep wells. There are four parts of the method that used in this study, there are water scarcity areas from the geological aspect interpreted based on geological, hydrogeological, and groundwater basin maps, meteorological aspects using the water balance method and drought index, distribution water installation analyzed from PDAM data, and drought information collection from interview. Based on a study on the identification of water scarcity areas in Kulon Progo Regency with geological and hydrogeological parameters, meteorological drought, PDAM and SPAM, and Interviews, it was found that 181 hamlets that having water-scarce in 35 villages in 11 sub-districts both covering areas that can be drilled and cannot be drilled. The number of water-scarce areas selected for groundwater drilling is 104 hamlets. The number of water scarcity areas in 1st priority is 37 hamlets, there are 21 helmets for 2nd priority, and 46 hamlets for 3rd priority.